Kriminalisasi Perbuatan Zina Sebagai Perwujudan Implementasi Sila Ketuhanan Yang Maha Esa dalam Rancangan Kitab Undang-undang Hukum Pidana (RKUHP) - Pratama, Memo Bayu (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Indonesia has become an independent nation and should have a criminal law which is the product of the nation itself. This is seen as a symbol and is a pride of a country that has been free from the snares of colonialism. It is the ideal of the Indonesian people to realize their own criminal law in accordance with the nation's ideology based on the values contained in Pancasila. This article discusses the criminalization of adultery in the New criminal law where in the old criminal law the act of adultery only concerns someone who is already bound into marriage. This study uses a juridical-normative research method (legal research) through the implementation of a statutory approach as well as a conceptual approach and analyzes available data sources using descriptive and qualitative data analysis methods. The results of this study can be concluded that criminalization related to adultery is a policy in criminal law reform that is based on the basic ideas of Pancasila.